Relations between somatotype and parametres of situational efficiency in top junior male basketball players - Jelicic, M.; Cavala, M.; Zivkovic, M. (FIS communications in Physical Education, Sport and Recreation, 2016)
The purpose of this research was to establish and explain the importance and characteristics of the relationship between somatotype and situational efficiency of top junior basketball players in five playing positions. A significant connection between somatotypes and percentage of two point shots as well as three point shots has been defined in the point guard position. Further on, the somatotype of the shooting guard position players show that there is only one significant regression indicating situational efficiency which is the connection with rebound. The somatotype of players in forward position shows one significant connection with indicators of situational efficiency in predicting blocked shots. Constitutional type of players in position of forward centre indicates, as in the previous two playing positions, one significant multiple regression analysis in which the connection between somatotype and the number of assists has been established. When it comes to somatotypes of players in centre position, the results show there is no significant connection with any variables of situational efficiency.